An Evaluation of Monetary Regime Options for Latin America - Berg, Andrew (IMF Working Papers; Working Paper ;, 2002)
We assess monetary regime options for Latin American countries. The costs of a common currency are likely to outweigh its benefits, as those countries face diverse economic shocks, do not trade much with each other, and are affected by common international financial shocks only to the same extent as the average pair of emerging markets. Unilateral dollarization would be desirable only for those countries where there are strong links to the U.S. economy, the credibility of the monetary authorities is irreversibly lost, and there is keen demand for dollar-denominated financial assets. Finally, some countries in the region seem to be good candidates for meaningful and useful floating.